Gênero e Contabilidade no Brasil: Qual é o saldo dessa conta? - Zabotti, Evellyn Danielly (2017)
The investigated subject in this study is on gender relation in accounting profession. The purpose was to verify the main constitutive factors of the gender relations in accounting profession, for the theme is considered as a research gap in Accountancy. As a theoretical platform, we choose the gender theory with the aim to interpret and subsidize the research data, collected through a survey, which characterize the research as quantitative, with the final sample of 948 accountants from Paraná. The data are qualitative and were analyzed by means of the independent testing, interpreted in the light of the gender theory. The research is, thus, based on the critical paradigm. As achieved results, we mention: the remuneration in the profession is influenced by biological gender, because there is a gender pay hierarchy in accounting profession; the difficulties and barriers in the exercise of the accounting profession as well as profession ascensions are influenced by the biological sex, condition that does not seem to be clearly identified by accountants, which allowed determining the presence of beta bias from the point of view of professionals; there is a concentration of women in the position of assistant and analyst and a higher concentration of men on senior positions of the organizational hierarchy; the accounting specialties in Paraná are articulated from the gender perspective, in other words, the more public the specialty is, the more it is realized as masculine, consequently, there is a higher remuneration linked to; the association of men and women characteristics are also articulated based on gender, in which women are perceived as emotional, understanding and determined, extending such associations to the accounting specialties; the notion that auditing is more related to objectivity while the personnel department is more related to sensibility. We justify these characteristics due to cultural definitions of masculine and feminine associated with some specific characteristics of certain occupations, which contributes to gender segregation of occupations as well as status assignments. The main constitutive principles of gender relation in Brazilian accounting profession include remuneration, glass ceiling, horizontal segregation and gender identities associated with the profession. As research limitations, we mention that the data, collected through a survey, reflect the perception of each professional about gender relation, which shows that the implications to the research to accounting profession include the necessity to calculate the value in women payment. This means that the class associations need to break the silence and the omission to institute specific regulation and control of the social discriminatory aspects of the profession. The contribution of this research to the accounting practice include the identification of the necessity to develop statements and review reports that show social inequality in organizations and the profession itself. There is still the need of educational institutions to include the thematic in its teaching and research agenda, because the skewed perspective of the professionals should be clarified. This research contributes to identify the means by which gender inequality is perpetuated in accounting profession, as identified in the biases of accountants that, in general, understand these inequalities as normal, perspective that is the base for such condition. There is a considerable field for gender studies in Accountancy in Brazil, thus, as a recommendation for future researches, it is suggested to include the historical survey of the entry of Brazilian women in accounting profession, using, therefore, the concept of “glass floor” proposed in this study which represents the initial conditions of work and entry which do not support women, also, qualitative researches in the grounded theory format, with the purpose to identify in the Brazilian context the variables or items of inequality that integrate the gender relations, and researches that recognize the experiences of men.